2006
DOI: 10.1038/sj.onc.1209566
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Sox4 expression by RNAi induces apoptosis in ACC3 cells

Abstract: Microarray RNA gene expression profiling analysis has shown that Sox4 (Sry-related high mobility group (HMG) box 4) is one of the most upregulated genes in adenoid cystic carcinoma (ACC), relative to non-neoplastic tissue of origin. Here, we show that Sox4 protein is similarly upregulated in ACC by immunohistochemistry of 28 primary cancers and 20 normal tissues. To elucidate the functional significance of these findings, RNA interference (RNAi)-mediated RNA silencing was used to downregulate Sox4 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 35 publications
5
70
0
Order By: Relevance
“…Fourteen genes with sixfold higher expression in the T3 tissues were identified and these were enriched with adhesion molecules (NRCAM, CD24, CTHRC1 and ROBO1) and transcription factors (FOXQ1, CDCA7 L, MYBL2 and SOX4); thus, these genes are candidate genes for direct involvement in tumor metastasis (Figures 1a and b). Overexpression of SOX4 has been shown to promote apoptosis in bladder carcinoma (Aaboe et al, 2006); in contrast, RNAi knockdown of SOX4 induces apoptosis in adenoid cystic carcinoma and prostate cancer (Liu et al, 2006;Pramoonjago et al, 2006). This suggests that the SOX4 molecular activity during caracinogenesis is influenced by additional factors that are enriched in a tissuespecific manner.…”
Section: Identification Of Genes Associated With Intrahepatic Metastamentioning
confidence: 81%
See 2 more Smart Citations
“…Fourteen genes with sixfold higher expression in the T3 tissues were identified and these were enriched with adhesion molecules (NRCAM, CD24, CTHRC1 and ROBO1) and transcription factors (FOXQ1, CDCA7 L, MYBL2 and SOX4); thus, these genes are candidate genes for direct involvement in tumor metastasis (Figures 1a and b). Overexpression of SOX4 has been shown to promote apoptosis in bladder carcinoma (Aaboe et al, 2006); in contrast, RNAi knockdown of SOX4 induces apoptosis in adenoid cystic carcinoma and prostate cancer (Liu et al, 2006;Pramoonjago et al, 2006). This suggests that the SOX4 molecular activity during caracinogenesis is influenced by additional factors that are enriched in a tissuespecific manner.…”
Section: Identification Of Genes Associated With Intrahepatic Metastamentioning
confidence: 81%
“…Empirical evidence suggested that SOX4 plays an important function in liver tumor metastasis as RNAi knockdown reduced HCC cell migration, invasion and intrahepatic metastasis in an orthotopic liver cancer model. This SOX4 function also seems to operate during breast cancer metastasis (Tavazoie et al, 2008) but not in other human cancer types (Aaboe et al, 2006;Liu et al, 2006;Pramoonjago et al, 2006). This suggests that SOX4 has diverse activities across various human cancers and that these are likely to be cell context-dependent, involving differential target activation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, SOX4 was also reported to be an oncogene for human prostate cancer cells (45), and SOX4 knockdown promotes apoptosis in adenoid cystic carcinoma cells (46). Thus, whether SOX4 is a tumor suppressor or an oncogene is presumably context-dependent, which is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SOX4 has been shown to be a transcriptional activator in lymphocytes (van de Wetering et al, 1993) and facilitates B and T cell differentiation (Schilham et al, 1996;Schilham et al, 1997). SOX4 gene expression is up-regulated in many tumor types, with experimental evidence suggesting that this contributes to cellular transformation (Liu et al, 2006;Shin et al, 2004), control of apoptosis (Liu et al, 2006;Pramoonjago et al, 2006;Aaboe et al, 2006;Ahn et al, 2002) and/or a metastatic phenotype (Liao et al, 2008;Tavazoie et al, 2008).…”
Section: Functionmentioning
confidence: 99%